Predictive Factors of Resistance to High-Dose Steroids Therapy in Acute Attacks of Neuromyelitis Optica Spectrum Disorder - Qin, Chuan; Tao, Ran; Zhang, Shuo-Qi; Chen, Bo; Chen, Man; Yu, Hai-Han; Chu, Yun-Hui; Shang, Ke; Wu, Long-Jun; Bu, Bi-Tao; Tian, Dai-Shi (Frontiers in Neurology, 2020)
High-dose steroids were the first-line therapy of acute attacks in neuromyelitis optica spectrum disorder (NMOSD), and were ineffective in the therapy of a proportion of NMOSD attacks. This study was aimed to explore possible predictors of resistance to high-dose steroids therapy. Demographics and disease characteristics of acute attacks were compared between attacks respond to high-dose intravenous methylprednisolone (IVMP) and the ones resistant to that. In total, 197 attacks in 160 patients were identified in our NMOSD registry. Compared with responders, attacks resistant to steroid had a trend of more previous use of immune suppressive drugs (25.5% vs 15.5%, p=0.080). Significant higher levels of proteins in CSF was found in non-responders than the responder (485.5 [388-656] vs 387 [291.5-532] mg/L, p=0.006). More active lesions were found in the brain stem of non-responders (8 attacks in 55, 14.5%), especially in pons (4 in 55, 7.3%) and medulla (8 in 55, 14.5%), as opposed to only 4.9% (7 patients in 142) in the responders. Multivariable logistic regression showed that resistance to high-dose steroid was associated to previous use of immune suppressive drugs (OR 2.31, 95%CI 1.002-5.34, p=0.049), CSF protein level above 450 mg/L (OR 3.42, 95%CI 1.72-6.82, p<0.001), and active lesions in brainstem (OR 3.80, 95%CI 1.17-12.32, p=0.026) In conclusion, patients with previous use of immunosuppressants, higher levels of CSF protein, and active lesions on brainstem are likely to show no response to a standalone treatment of high-dose IVMP during acute attacks of NMOSD.